Cooperation and Innovation Performance in Rural, Low-Technology Regions - Daniel Schiller; Stephan L. Thomsen; Pia Wassmann (European Regional Science Association (ERSA), 2014)
This paper assesses the extent to which cooperation impacts innovation performance of firms in rural regions characterized by a solid economic performance despite a low-technology industrial structure. Particular emphasis is placed on the spatial and functional dimension of cooperation. Generic results for the German region of Lower Bavaria show that firms do not profit primarily from R&D-intensive forms of cooperation, but that other forms of cooperation are more important for regional firms. For policymakers, this implies that an exclusive focus on R&D-based regional innovation policies may be neither appropriate nor sufficient for stimulating innovativeness in this type of region.
Keywords: R11; O18; O31; L25; 330; innovation; connectivity; low-tech industries; rural region; R&D; Germany